Kepemilikan Institusional, Likuiditas, Capital Expenditure, Profitabilitas dan Corporate Cash Holding di Masa Pandemi Covid-19 - Ikhsani, Misyka Qalbiya Nugrha; Gurendrawati, Etty; Nasution, Hafifah (E-Jurnal Akuntansi, 2022)
This study aims to determine how the influence of institutional ownership, liquidity, Capital Expenditure, and profitability on corporate cash holding (CCH) during the Covid-19 Pandemic. The research population is trading, service and investment sector companies listed on the Indonesia Stock Exchange (IDX) in 2020. The sample is 115 using purposive sampling technique. This study uses multiple linear regression analysis, with the type of secondary data processed through the IBM SPSS version 25 application. The results showed that institutional ownership and Capital Expenditure had no effect on CCH. Meanwhile, liquidity and profitability have a positive effect on CCH. Keywords: Corporate Cash Holding; Institutional Ownership; Liquidity; Capital Expenditure; Profitability